Convective heat transfer, friction factor and thermal performance in a round tube equipped with the modified V-shaped baffle - Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2018)
Convective heat transfer, pressure loss and thermal performance in a heat exchanger tube inserted with the modified V-shaped baffle are investigated numerically. The influences of the flow attack angle (α = 20o, 30o and 45o), baffle height in term of blockage ratio (b/D = BR = 0.05, 0.10, 0.15, 0.20 and 0.25) and arrangement (The V-tip pointing downstream is called “V-Downstream”, while the V-tip pointing upstream is named “V-Upstream”.) on heat transfer and friction loss are presented for the Reynolds number in range 100 – 1200 (laminar region). The numerical study (finite volume method) is selected to solve the current investigation and to describe the mechanisms inside the heat exchanger tube. The flow visualizations and heat transfer characteristics in the heat exchanger tube are plotted in the numerical-result report. The results on heat transfer, friction factor and thermohydraulic performance of the test tube are compared with the smooth circular tube. It is found that the vortex strength in the heat exchanger tube is an important factor to enhance heat transfer rate and thermal performance. In addition, the maximum thermal enhancement factor is around 3.22 at α = 30o, BR = 0.2, Re = 1200 for V-Upstream arrangement.
Keywords: Baffle; Convective heat transfer; Flow visualization; Heat exchanger tube; Thermal performance